The Impact of Dairy Effluent on Germination Parameters of Seeds of Mung bean (Vigna radiata) and Mustard (Brassica nigra) - Kapil, Jyoti; Mathur, Neetika (International Journal of Economic Plants, 2020)
The advancement of a country depends upon its industrialization. Of all industrial sectors, the food processing units have highest consumption of water and are biggest producers of effluent per unit of production.The concentration and composition of the effluent depends upon operating methods andthe size and design of the processing plant.The dairy industry generates on an average 6-10 litres of waste water per litre of the milk processed. It has relatively high organic matter, suspended solids, trace organic nutrients which are essential for growth of crop plant. Thus, the utilization of the dairy effluent for irrigation can be an eco friendly approach for its disposal. The present study was carried out to study the influence of dairy effluent on seed germination, seedling growth and biomass production in mung bean (Vigna radiata) and mustard (Brassica nigra). The seeds of both the plant species were grown in petriplates and pots irrigated with various concentrations of dairy effluent (20, 40, 60, 80 and 100%). The dairy effluent concentration of 20% was more favorable for total growth parameters viz., the germination percentage, the shoot length, dry weight and wet weight both in mustard and mung bean. Among different concentrations, 100% concentration of effluent caused inhibitory effect. Thus, it is recommended that only after suitable dilution, the dairy effluent can be effectively used for irrigation.